Evaluation of petroleum potential of the Balkassar block potwar basin Pakistan, with integrated interpretation of source, reservoir and structure / Syed Bilawal Ali Shah - Syed Bilawal , Ali Shah (2019)
Potwar Basin is known to be one of the greatest and oldest oil producing provinces in Pakistan. The subsurface of Potwar Basin consists of large subsurface anticlines, mostly bounded by thrust and reverse faults. The area selected for this study is in Balkassar Oilfield situated in Potwar Basin, which is a compressive region belonging to the active foreland fold and thrust belt of northern Pakistan. In this study, subsurface structure and hydrocarbon potential of the subsurface has been evaluated based on seismic structural interpretation, source and reservoir rock evaluation. An attempt was made to interpret subsurface structure geology and hydrocarbon potential by identifying reflectors, folds, faults, structural trends, styles and trap type using well logs and 2D seismic data. Interpretation reveals the presence of an anticline in the center of the area, bounded by seven major blind faults, four faults are present at south-eastern limb, two faults are present in the north-western limb. The six major faults that bound the structure were previously the normal faults but were reactivated as reverse faults by salt diapirism. In the seismic grid line moving in northeast direction towards center an increase in disturbance can be observed. This structure in the subsurface of the Balkassar block is recognized as a salt-cored anticline structure formed as a result of Indian Plate subduction of an anticlockwise drift and Himalayan orogenic forces. Balkassar structure is at stage 2 known as active diapirism pillow stage. 3D maps show anticline structure is dipping steeply towards northwest side, however, it is dipping gently in southeast side, whereby the limbs have been terminated by the faults present on both sides of the anticline. Chorgali Formation in the subsurface of Balkassar block is covering anticline top flat surface, and the contour map indicates a structural trend that is a four way closure that could host hydrocarbons accumulation. Furthermore, at the level of Sakesar Limestone in the northwest side, a broad contour closure has been identified which may act as a potential prospect for hydrocarbon accumulation bounded by faults from both sides. Source rock analysis was performed on the Patala Shale Formation from two outcrop sections to evaluate their hydrocarbon generative potential. These samples were analyzed using organic geochemical methods (TOC, Rock-Eval and Py-GC) and organic petrological analysis (vitrinite reflectance). The TOC content of the shales ranges between 0.25 - 1.16 wt. %, while the S2 values are from 0.11-0.63 mg HC/g rock, consequently low HI values (18-294 mg HC/g TOC) were obtained, thus indicating poor to fair hydrocarbon potential. This is supported by the absence of distinct hydrocarbon peaks in the pyrolysis-GC pyrograms. Observation under the microscope showed the dominant presence of vitrinitic (Type III kerogen) and inertinitic (Type IV kerogen) phytoclasts with minor amount of amorphous organic matter (Type II kerogen). The measured vitrinite reflectance (%Ro) values vary between 0.51-0.84%, indicating immature to peak oil generation window. On the basis of Tmax values (385 to 429 °C), these samples are immature for hydrocarbon generation, however, these values appear to have been affected by the low S2. Evaluation of the reservoir rocks was conducted based on well log analysis on the Sakesar and Chorgali formations encountered in three wells. Both formations are shown to possess good reservoir qualities. Sakesar Formation has an average porosity of up to 11.77% and permeability reaches up to 115.81 mD. Having average porosity of 18.13%, the Chorgali Formation has a better potential to act as reservoir rocks compared to the Sakesar Formation in the Balkassar Oilfield.